Analisis Penerapan Standar Akuntansi Pemerintahan Desa pada Kantor Desa Gumulan Kecamatan Kesamben Kabupaten Jombang - Nur Hamidah, Anggih; Ghofirin, Mohammad (JURNAL AKUNTANSI DAN MANAJEMEN, 2025)
This research investigates the implementation of Village Government Accounting Standards (SAPDesa) in the financial management of Gumulan Village, located in Kesamben District, Jombang Regency, during the 2022 fiscal year. Employing a qualitative method with a phenomenological approach, the study aims to understand how the village government applies SAPDesa in the processes of planning, implementation, reporting, and accountability. Data were collected through observation, documentation, and in-depth interviews with key village officials including the village head, secretary, financial staff, and members of the Village Consultative Body (BPD). The findings indicate that the village has generally followed the financial management procedures outlined in Permendagri Regulation No. 20 of 2018. Financial planning was conducted through participatory village meetings and resulted in the formulation of the RKPDesa and APBDesa documents. However, there was a delay in the ratification of the village budget. During implementation, financial transactions were recorded using the General Cash Book and supporting ledgers. The financial reports consisted of the Budget Realization Report (LRA) and Notes to Financial Statements (CaLK), but the village had not yet compiled a complete balance sheet or asset report. In terms of accountability and transparency, the village has made efforts to involve the community by providing access to financial information through village meetings and public information boards. Overall, the village government has demonstrated a commitment to transparent and accountable financial practices, although improvements are still needed in documentation and timely reporting. This research contributes to the understanding of public sector accounting practices at the village level and highlights the importance of strengthening governance through standardized reporting.